Modeling of Leakage Currents in Double Gate MOSFET - Kushwaha, Madhu (Electronics and Communication Engineering, 2022)
This thesis is aimed to present the modeling of leakage currents in double gate (DG) metal oxide semiconductor field effect transistor (MOSFET) at nanoscale. The thesis mainly focuses on the estimation of gate tunneling current and subthreshold leakage current in the symmetrical DG MOSFET architecture. The developed models are then validated with the available experimental results / published models. Firstly, a theoretical background has been developed with the modeling of gate tunneling current in single gate (SG) MOSFET structure at nanoscale. The analytical model has been presented considering varying surface potential with applied voltage for evaluating gate tunneling current through thin dielectrics in nanoscale MOSFETs. The electron wavefunction has been calculated by treating the band profile in the channel as a triangular potential well. The tunneling probability through the gate oxide has been evaluated using Jeffreys–Wentzel–Kramers–Brillouin (JWKB) approximation method. The tunneling current density is estimated from the evaluated interface wavefunction along with the tunneling probability. The obtained model is validated with published as well as experimental results. Next, the analytical model is developed for gate tunneling current in nanoscale DG MOSFET on the basis of carrier-energy quantization in the channel. It is essentially an extension of the work on modeling of gate tunneling current in n-channel single gate MOSFET structure at nanoscale. The analytical solution for the potential distribution has been obtained by applying Poisson’s equation considering both inversion and depletion charges in the silicon body and solved using perturbation approach. The appropriate use of electron wave function at the interfaces along with the tunneling probability through the oxide has led to the estimation of tunneling current density. The results obtained are validated with published model. The estimation of subthreshold leakage current is based on potential solution using perturbation approach in combination with parabolic potential approximation. Two dimensional (2D) Poisson’s equation has been solved using parabolic potential approximation. The obtained potential profile is then compared with the one evaluated using perturbation approach. Once the anticipated potential profile is available the inversion charge is obtained and the subthreshold leakage current caused by both drift and diffusion has been calculated. The estimated subthreshold leakage current is validated with experimental results. The developed analytical models are found to be simple, involving less number of parameters and provide easy-to-use expressions for the quick estimation of leakage currents in nanoscale DG MOSFETs.
Electronics and Communication Engineering Department
Keywords: Double gate MOSFET; Gate tunneling current; Subthreshold leakage current; Electrical confinement; Structural confinement